Relationship between patient safety culture and patient experience in hospital settings: a scoping review - Adel Alabdaly; Reece Hinchcliff; Deborah Debono; Su-Yin Hor (BMC, 2024)
Abstract Background Measures of patient safety culture and patient experience are both commonly utilised to evaluate the quality of healthcare services, including hospitals, but the relationship between these two domains remains uncertain. In this study, we aimed to explore and synthesise published literature regarding the relationships between these topics in hospital settings. Methods This study was performed using the five stages of Arksey and O'Malley's Framework, refined by the Joanna Briggs Institute. Searches were conducted in the CINAHL, Cochrane Library, ProQuest, MEDLINE, PsycINFO, SciELO and Scopus databases. Further online search on the websites of pertinent organisations in Australia and globally was conducted. Data were extracted against predetermined criteria. Results 4512 studies were initially identified; 15 studies met the inclusion criteria. Several positive statistical relationships between patient safety culture and patient experience domains were identified. Communication and teamwork were the most influential factors in the relationship between patient safety culture and patient experience. Managers and clinicians had a positive view of safety and a positive relationship with patient experience, but this was not the case when managers alone held such views. Qualitative methods offered further insights into patient safety culture from patients' and families' perspectives. Conclusion The findings indicate that the patient can recognise safety-related issues that the hospital team may miss. However, studies mostly measured staff perspectives on patient safety culture and did not always include patient experiences of patient safety culture. Further, the relationship between patient safety culture and patient experience is generally identified as a statistical relationship, using quantitative methods. Further research assessing patient safety culture alongside patient experience is essential for providing a more comprehensive picture of safety. This will help to uncover issues and other factors that may have an indirect effect on patient safety culture and patient experience.